Histone lysine crotonylation during acute kidney injury in mice - Olga Ruiz-Andres; Maria Dolores Sanchez-Niño; Pablo Cannata-Ortiz; Marta Ruiz-Ortega; Jesus Egido; Alberto Ortiz; Ana Belen Sanz (The Company of Biologists, 2016)
Acute kidney injury (AKI) is a potentially lethal condition for which no therapy is available beyond replacement of renal function. Post-translational histone modifications modulate gene expression and kidney injury. Histone crotonylation is a recently described post-translational modification. We hypothesized that histone crotonylation might modulate kidney injury. Histone crotonylation was studied in cultured murine proximal tubular cells and in kidneys from mice with AKI induced by folic acid or cisplatin. Histone lysine crotonylation was observed in tubular cells from healthy murine and human kidney tissue. Kidney tissue histone crotonylation increased during AKI. This was reproduced by exposure to the protein TWEAK in cultured tubular cells. Specifically, ChIP-seq revealed enrichment of histone crotonylation at the genes encoding the mitochondrial biogenesis regulator PGC-1α and the sirtuin-3 decrotonylase in both TWEAK-stimulated tubular cells and in AKI kidney tissue. To assess the role of crotonylation in kidney injury, crotonate was used to increase histone crotonylation in cultured tubular cells or in the kidneys in vivo. Crotonate increased the expression of PGC-1α and sirtuin-3, and decreased CCL2 expression in cultured tubular cells and healthy kidneys. Systemic crotonate administration protected from experimental AKI, preventing the decrease in renal function and in kidney PGC-1α and sirtuin-3 levels as well as the increase in CCL2 expression. For the first time, we have identified factors such as cell stress and crotonate availability that increase histone crotonylation in vivo. Overall, increasing histone crotonylation might have a beneficial effect on AKI. This is the first observation of the in vivo potential of the therapeutic manipulation of histone crotonylation in a disease state.